Parental Factors Related to COVID-19 Prevention Behavior in Children with Intellectual Disability: Partial Least Square Structural Equation Modeling - Chairijah, Zumrotul; Rahfiludin, M. Zen; Margawati, Ani; Ediati, Annastasia (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Efforts to prevent COVID-19 in children with intellectual disability require the role of parents. Even though the vaccine has been implemented, the most important effort is to implement health protocols. Implementing health protocols cannot be separated from knowledge, attitudes, intentions, subjective norms, and social support from parents. This research aims to determine the influence of knowledge, attitudes, intentions, subjective norms, and social support on the COVID-19 prevention behavior of parents of children with intellectual disability. This type of research is descriptive correlational research, and the developed model is validated using the partial least squares structural equality modeling (PLS-SEM) approach based on data collected from 100 parents of children with intellectual disabilities taken using purposive sampling at Semarang Municipal Special Schools.The study results show that parental characteristics, namely education, influence attitudes, which can ultimately affect parental intentions. Parental education also affects social norms, namely social support and subjective norms, which can determine COVID-19 prevention behavior. Parental education is a priority in public health strategies because it can directly shape attitudes, intentions, and social norms that can improve the health of children with intellectual disabilities. Health programs and education for parents must be focused and carried out consistently and continuously.